Kepemilikan Manajerial, Institusional, Dewan Komisaris Independen, Komite Audit dan Kinerja Keuangan Perusahaan Food and Beverage - Agatha, Bella Riantiarta; Nurlaela, Siti; Samrotun, Yuli Chomsatu (E-Jurnal Akuntansi, 2020)
This study aims to examine and analyze the effect of managerial ownership, institutional ownership, independent board of commissioners, and audit committee on the financial performance of food and beverage companies listed on the Indonesia Stock Exchange in the 2014-2018 period. This type of research is quantitative research. The population and sample used by all food and beverage companies listed on the Indonesia Stock Exchange in the 2014-2018 period by taking samples using purposive sampling method obtained a total of 13 companies that met the criteria. The data analysis technique used is multiple linear regression test. The results of this study indicate that managerial ownership, independent boards of commissioners, and audit committees have a positive and significant influence on financial performance. While institutional ownership has no effect on financial performance. Keywords: Financial Performance; Managerial Ownership; Institutional; Independent Board of Commissioners; Audit Committee.